2017
DOI: 10.1007/978-3-319-60733-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Identifying Novel Targets in Precision Medicine: Lessons from DNA Repair

Abstract: Genome stability is maintained by a number of elegant mechanisms, which sense and repair damaged DNA. Germline defects that compromise genomic integrity result in cancer predisposition, exemplified by rare syndromes caused by mutations in certain DNA repair genes. These individuals often exhibit other symptoms including progeria and neurodegeneration. Paradoxically, some of these deleterious genetic alterations provide novel therapeutic opportunities to target cancer cells; an excellent example of such an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…The synthetic lethal interactions are utilized by these kinds of therapy to design personalized medicine which depends on the patient's molecular profiling and behavior of cancer cells. Several benefits of using patient profiling starting from the determination of drug resistance after relapse, could also help in adjusting the therapeutic dose [155]. Precision medicine is a new type of treatment that plays a critical role in selecting the most appropriate therapy at the suitable time, as it only succeeds in targeting the DNA repair pathway in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic lethal interactions are utilized by these kinds of therapy to design personalized medicine which depends on the patient's molecular profiling and behavior of cancer cells. Several benefits of using patient profiling starting from the determination of drug resistance after relapse, could also help in adjusting the therapeutic dose [155]. Precision medicine is a new type of treatment that plays a critical role in selecting the most appropriate therapy at the suitable time, as it only succeeds in targeting the DNA repair pathway in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of proteins involved in the DNA damage response process has been described in a number of age-dependent diseases, including cancer, as well as progeroid syndromes. Therefore, modulation of DNA repair signaling pathways directly, or through their epigenetic regulation, is one of the potential therapeutic strategies [ 747 , 1100 , 1101 ]. In particular, the brain is an organ with a high level of oxygen and energy consumption.…”
Section: Pharmacological Interventions Protecting Genomementioning
confidence: 99%
“…In addition, there is still rise the survival rate of patients for adjustment in the formulation of treatment plans. Nowadays, more and more studies have found that the recurrence and metastasis of tumors are closely related to the DNA repair regulatory system related to drug resistance [22][23][24].…”
Section: Discussionmentioning
confidence: 99%